Evaluation of the impact of 13-valent pneumococcal conjugate vaccine immunization in children by surveillance of culture-confirmed pneumococcal disease: A prospective clinical microbiological study. Issue 36 (23rd August 2019) - Chen, Chih-Ho; Su, Lin-Hui; Li, Hsin-Chieh; Hsu, Mei-Hua; Wu, Tsu-Lan; Chen, Chyi-Liang; Kuo, Kuang-Che; Hsiao, Chang-Chun; Chiu, Cheng-Hsun
Highlights: Serotype replacement occurred quickly after the use of PCV13. Surveillance of CCPD appears superior to IPD alone for evaluation of overall impact. The proportion of NVTs increased, but the CCPD incidence caused by NVTs did not. Abstract: The study aimed to investigate the impact of 13-valent pneumococcal conjugate vaccine (PCV13) immunization on the overall pneumococcal disease in children in Taiwan by surveillance of culture-confirmed pneumococcal disease (CCPD). This study was conducted in a medical center from 2012 to 2016. Clinical isolates of Streptococcus pneumoniae were prospectively collected from pediatric patients. Serotyping, multi-locus sequence typing, and antimicrobial susceptibility testing were performed. A total of 473 patients with CCPD, including 58 with invasive pneumococcal disease (IPD), were identified. The incidence of CCPD per 10, 000 admissions decreased from 71.7 in 2012 to 27.0 in 2016. The proportion of additional PCV13 serotypes significantly decreased from 52.0% in 2012 to 21.7% in 2015 but increased slightly to 26.7% because of serotype 19A in 2016 ( P  < 0.0001). The proportion of non-vaccine serotypes (NVTs) increased significantly from 18.4% in 2012 to 66.7% in 2016, but the increase of the incidence of CCPD caused by NVTs was not considered significant ( P  = 0.0885). Genotyping identified predominant clones, ST63 15A, ST83 15B, and ST166/338 23A, for major NVTs. The penicillin non-susceptibility of PCV13 serotypes was significantly higher than that of NVTs ( P  < 0.0001). Surveillance of CCPD appears superior to IPD alone for evaluation of the overall impact of pneumococcal immunization. Serotype replacement occurred quickly after the use of PCV13, while the incidence of NVT infection did not show a significant increase in children over the years. The gradual introduction of PCV13 into national immunization program is effective in reducing overall pneumococcal disease in children.